Bus monioring system (hardware part) - Nasrung, Nurba (2008)
Vehicle monitoring system has become very famous method in engineering field these days to monitor any types of break down, vehicle behavior, fuel consumption including safety and health and many more. Bus Monitoring System was the other types of vehicle monitoring system and categorized in public transport monitoring system. The purpose of this project is to monitor the movement of public bus in the road using RF communication system. Along the way of the destination of the bus, it will arrive at few bus stops. Each time the buses reach the bus stop the driver will send the bus ID to the bus stop using RF Transmitter. Then it will help the officer to record the bus ID from the bus stop and ensure that the bus follow the right destination. In order to make this process succeed, each bus stop must have its own RF receiver to collect the bus ID that was sends from the bus. Hence, the circuit design must consist of RF module, PIC microchip, matrix keypad and also LCD to display the output. There will be two hardware constructed for this project which called transmitter board and receiver board. Transmitter board will be plugged in inside the bus and receiver board is placed at the bus stop in a safe area. Both hardware must have main control panel such as microcontroller or other microprocessors to ensure all the process in both side run smoothly.